In Situ Partial-Cyclized Polymerized Acrylonitrile-Coated NCM811 Cathode for High-Temperature ≥ 100 °C Stable Solid-State Lithium Metal Batteries - Jiayi Zheng; Haolong Jiang; Xieyu Xu; Jie Zhao; Xia Ma; Weiwei Sun; Shuangke Liu; Wei Xie; Yufang Chen; ShiZhao Xiong; Hui Wang; Kai Xie; et al. (Nano-Micro Letters)
Highlights Uniform and stable interfacial layer with both ionic and electronic conduction on the surface of solid-state composite cathode by in situ polymerization cyclization treatment. Theoretical calculations demonstrate that cPAN can effectively inhibit transition metal dissolution and uneven cyclic stress distribution and improve the stability of the crystal structure. In-cPAN-260@NCM811 has excellent cycling performance with 86.8% retention after 300 cycles and thermally safe stability at high-temperature extremes.